MANAGEMENT PRACTICES: SHAPING EMPLOYEE SATISFACTION AND COMMITMENT IN LARGE GERMAN COMPANIES - Sosnovika, Lana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The rapid evolution of the political, economic, and social landscape has generated increased interest in understanding the contextual application of Management styles and behaviours toward employees. In this context, organizations must comprehend and assess employee satisfaction to enhance productivity and realize their strategic and economic goals. Therefore, this study aims to investigate the prevailing and significant Management behaviours toward employees in large German companies and their impact on employee satisfaction and job commitment. To achieve the research objective, the study will employ a qualitative method to explore Management behaviours toward employees. Data was collected through interviews with randomly selected Managers from different companies and departments. The study aims to uncover discrepancies or variations in employee expectations regarding Management behaviour. The findings will provide a better understanding of the most prevalent and significant Management behaviours toward employees in large German companies and their impact on employee satisfaction and job commitment. The results will be valuable to Management in adopting suitable leadership styles and improving employee satisfaction, leading to increased productivity and organizational performance. The research will contribute to the existing body of knowledge in the field of Management and human resource Management by providing insights into the impact of Management behaviours on employees. It will also offer recommendations to Management on how to enhance employee satisfaction and job commitment, leading to improved organizational performance. In conclusion, this study will investigate the prevailing Management behaviours toward employees in large German companies and their impact on employee satisfaction and job commitment.